Saint Yared’s Cosmic Harmony: Music, Astronomy, and Philosophy in 6th-Century Ethiopia - Claire Dubois (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2011)
Saint Yared, a 6th-century Ethiopian composer and theologian, is widely recognized for pioneering an indigenous system of musical notation through the melekket system and the Deggua antiphonary. However, his interdisciplinary contributions particularly the integration of music, astronomy, and philosophy remain underrepresented in global scholarship. This study seeks to re-evaluate Yared’s intellectual legacy by situating his work within broader discourses in world musicology and the history of ideas. Employing qualitative research methods, this study analyzes Ge’ez manuscripts, ethnomusicological recordings, and historical accounts through textual interpretation, comparative analysis, and thematic synthesis. It examines the cosmological dimensions of Deggua, the theological structure of Yared’s musical modes (Ge’ez, Ezel, and Araray), and the epistemological foundations of the melekket notation system. Particular attention is given to the influence of Aksumite traditions and the transmission of Byzantine thought through the Nine Saints. The findings reveal that Yared’s Deggua exhibits a structured alignment with liturgical seasons and celestial cycles, suggesting an embedded understanding of astronomical rhythms. His modal system reflects Trinitarian theological principles while also resonating with Neoplatonic concepts of cosmic harmony. Furthermore, the melekket notation system predates and conceptually parallels early European notational developments, challenging dominant Eurocentric narratives that center figures such as Guido d’Arezzo and Boethius.